A Multicultural Approach to Improving Students' Understanding of Bullying at Cibeber Mandiri 2 Elementary School, Cimahi City - Sri Rohartati; Deasy Rahmawati; Lisdayanti Nuratifah; Eri Subekti (Journal of Elementary Education, 2025)
This study aims to describe the application of a multicultural approach in improving students' understanding of the concept of bullying at SD Negeri Cibeber Mandiri 2. The focus of the study includes three things: describing the process of applying a multicultural approach, analyzing significant differences between pretest and posttest results, and measuring improvements in student understanding. The research method used a quantitative approach with a one-group pretest-posttest design. The research population consisted of 52 students, with 26 students as the sample. The multicultural approach was implemented in three sessions that emphasized multicultural values and their relevance to the issue of bullying. The results showed a consistent increase in scores from the first to the third session. The Paired Sample T-Test analysis showed a very significant difference between the pretest and posttest results with a p-value of 0.000. The N-Gain analysis showed that the average increase was in the moderate category with a value of 0.48, which means that this approach is effective, but the results are not uniform across all students. Some students showed very high increases, while others showed low or even negative increases. This confirms the need for more differentiated learning strategies in order to optimally accommodate the needs and characteristics of students.